2020
DOI: 10.1371/journal.pone.0243253
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning based automatic segmentation of metastasis hotspots in thorax bone SPECT images

Abstract: SPECT imaging has been identified as an effective medical modality for diagnosis, treatment, evaluation and prevention of a range of serious diseases and medical conditions. Bone SPECT scan has the potential to provide more accurate assessment of disease stage and severity. Segmenting hotspot in bone SPECT images plays a crucial role to calculate metrics like tumor uptake and metabolic tumor burden. Deep learning techniques especially the convolutional neural networks have been widely exploited for reliable se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…U-Net has been proven to possess the potential for bone metastases segmentation. Lin et al (19) built two deep learning networks based on U-Net and Mask R-CNN to segment hotspots in bone SPECT images for automatic assessment of metastasis. Their results showed that the U-Net-based model achieved better segmentation performance with a precision and recall value of 0.76 and 0.67 than the Mask R-CNN model (precision, 0.72; recall, 0.65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…U-Net has been proven to possess the potential for bone metastases segmentation. Lin et al (19) built two deep learning networks based on U-Net and Mask R-CNN to segment hotspots in bone SPECT images for automatic assessment of metastasis. Their results showed that the U-Net-based model achieved better segmentation performance with a precision and recall value of 0.76 and 0.67 than the Mask R-CNN model (precision, 0.72; recall, 0.65).…”
Section: Discussionmentioning
confidence: 99%
“…The U-Net algorithm is one of the most commonly used deep learning-based convolutional neural networks (CNNs) ( 13 ), which shows potential in detection, segmentation, and classification of metastatic lesions on MRI images such as brain metastases ( 14 , 15 ) and liver metastases ( 16 ). Concerning the automated bone metastasis analysis using the deep learning technique, the research trend is mainly on BS ( 17 , 18 ) and single-photon emission computerized tomography (SPECT) images ( 19 , 20 ); less attention has been paid to the diagnosis of mpMRI ( 21 , 22 ). To this end, we intend to apply the 3D U-Net ( 23 ) algorithm for the segmentation of bone metastases on mpMRI images.…”
Section: Introductionmentioning
confidence: 99%
“…20 DL auto-segmentation of metastatic deposits on bone SPECT studies to improve staging and determining tumor burden. 21 DL and FDG PET/CT were used to predict (89% accuracy) treatment outcomes in patients with oral squamous cell carcinoma. 22 Detection of seizure foci on FDG brain PET was also enhanced, regardless of ictal or interictal status, with CNN based DL applications in pediatric patients with the DL framework.…”
Section: The Goblet Of Firementioning
confidence: 99%
“…Existing work mainly focuses on the development of CNN-based automated classification models for identifying bone lesions metastasized from multiple primary solid tumors [3,4], prostate cancer [5,[7][8][9], and breast cancer [6]. In our previous work, we developed CNN-based models to identify bone metastasis with thoracic SPECT scintigraphic images [12] and to segment the metastasized lesions from thoracic SPECT scintigraphic images [13].…”
Section: Introductionmentioning
confidence: 99%